The quantitative evaluation of alternaria toxins in apple and tomato juices - Topdemir, Aykut; Gür, Nazmi (My University, 2016)
In this study we aimed to quantify the alternariol (AOH), alternariol monomethyl ether (AME) and tenuazonic acid (TEA) in 10 different brands of tomato and apple juices by HPLC (high pressure liquid chromatography). In tomato juice, it was found that AOH quantity varies in a range of 1,95x10-3 - 8,30x10-3 ?g/mL, AME of 1,22x10-4- 4,28x10-2 ?g/mL and TEA between 4,0x10-2 and 2,38 ?g/mL. In apple juice, it was determined that the range of AOH quantity is 6,11x10-4- 0,25 ?g/mL, the AME quantity is 2,03x10-4–3,92x10-3 ?g/mL and the range of TEA is 0,32 -9,62 ?g/mL. The differences among tomato juice and apple juice samples, may have resulted from the fruit’s harvest time, harvest type, transport, processing, storage and shelf life in markets.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Alternariol (AOH); Alternariol monomethyl ether (AME); Tenuazonic acid; (TEA); tomato juice; apple juice